Study on shear force distribution in structural design of BRBF structure with high β value. (15th August 2019) - Li, Qi; Liu, Huijuan; Wang, Tiancheng; Bao, Enhe
Highlights: Seismic static equivalent value of columns may be underestimated by bottom shear method. Modified bottom shear method suitable for multi-story BRBF structure with high- β is proposed. Seismic responses of frame vibration model and particle system model are compared and analyzed. The rationality of the modified bottom shear method is verified. Abstract: In order to realize the optimum distribution of story shear force for multi-story BRBF structures with high β value, elastic–plastic time history analysis is carried out for the frame vibration model ( B S ) with β of 0.9 and the particle system model ( S 0, S 1, S 2 ) based on the bottom shear method and the modified bottom shear method, the story shear force, story drift, maximum overturning moment and the seismic response of supporting column are compared and studied. The results are as follows: The story response values of B S are in good agreement with the particle system vibration model in the middle and low floors, and the upper floors are close to the particle system vibration model S 0, S 1 and S 2 . When static pushover method is used in seismic design, the results of B i1 and B i2 model analysis of modified bottom shear method are more consistent with the actual situation; When the bottom shear method is used to design multi-story BRBF with high β value, there exist the possibility that the seismic static equivalent value of the structural column is underestimated and there is a certain degree of potential safety hazard; Under strong earthquakes, the influence of the second mode of vibration on the overall response is considerable and the upper floors are more reactive.